Resultant knee joint moments for lateral movement tasks on sliding and non-sliding sport surfaces - Nigg, B. M.; Stefanyshyn, D. J.; Rozitis, A. I.; Mündermann, A. (Journal of Sports Sciences, 2009)
The aim of this study was to compare ankle and knee joint moments observed when playing on sport surfaces that slide slightly relative to the ground with the moments observed when playing on conventional sport surfaces. Three-dimensional resultant internal joint moments and kinematic characteristics of the lower extremity were quantified for 21 university basketball players when performing v-cut and side-shuffle tasks on three types of sliding surface (interlocking tiles) and on two types of conventional surface (maple wood and rolled vinyl). Translational and rotational friction between the five test surfaces and a test shoe were also quantified. The five sport surfaces moved horizontally between 0.2 and 1.6 mm during the landing phase of the two tasks. The medio-lateral ground reaction forces were lowest for the surfaces with the highest horizontal movement. Resultant ankle joint moments were lower and resultant knee moments were higher on the sliding surfaces than the conventional surfaces. Sport surfaces that allow a few millimetres of horizontal movement during ground contact may reduce joint loading at the ankle joint, but increase joint loading at the knee joint, when compared with conventional sport surfaces, and thus may influence the prevalence of knee injuries.